A key to species of the leafhopper genus Tambocerus (Hemiptera, Cicadellidae, Deltocephalinae) with description of a new species from Pakistan - Naveed, Hassan; Zhang, Yalin (Zootaxa, 2018)
The leafhopper genus Tambocerus Zhang & Webb is reported from Pakistan for the first time with the description of a new species, Tambocerus bulbulus sp. nov. A species checklist with distribution summary and a key to species for males are provided.